Kesahihan dan Ke-DaâÃf-an HadÃ®th âPerkara Halal Yang Paling Dibenci Allah adalah Talakâ dan Implikasinya Terhadap Konsep Talak - Amrulloh, Amrulloh (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
The study deals with the discussion about the validity of hadÃ®th about âthe most despised matter by God is divorceâ and its invalidity as well as the implication of each status of sahÃ®h and daâÃ®f which rests in the hadÃ®th towards the concept of lawfulness and detestation of divorce. For certain group of people this hadÃ®th might seem wise, since it would be able to significantly decrease the number of divorce or to be a sort of âan ultimate weaponâ for judge or parents to give advice for spouse who experience domestic rift. However, for other people the hadÃ®th seems inconsistent. They argue that it is impossible for God to hate a lawful matter. Therefore, the hadÃ®th is unique, since it is validated by a number of prominent Muslim scholars on one hand. On the other, there are also a number of noticeable Muslim scholars who believe the hadÃ®th as daâÃ®f. Each group, however, build their argument on a common ground, i.e. conventional science of the critique of hadÃ®th.